Acrolein oxidation catalyst and preparation process thereof
By preparing an acrolein oxidation catalyst with SiO2 crystal form and specific atoms, the shortcomings of the existing catalysts in terms of structural stability and acrylic yield are solved, and efficient acrolein conversion and acrylic selectivity are achieved.
Patent Information
- Application Number
- CN202411933711.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-26
- Publication Date
- 2025-04-04
AI Technical Summary
The existing acrylic catalysts for oxidation of acrolein have room for improvement in the structural stability of the catalyst and the yield of acrylic acid.
A new acrylic oxidation preparation acrylic acid catalyst is provided, with atomic composition of MoaVbCucSbdWeSifCgOh, with crystal forms of SiO2, including small nanoparticles and irregular large particles. Through a specific preparation process, including preparation solution, solution mixing reaction, drying, crushing, forming and calcining steps, forming a catalyst with high catalytic activity and structural stability.
The catalyst has good crystallinity and catalytic activity, can improve the yield of acrolein and the selectivity of acrylic acid, and has good structural stability, extending the service life of the catalyst.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalyst production, in particular to an acrolein oxidation catalyst and a preparation process thereof. Background Art
[0002] Acrylic acid is an organic compound with the chemical formula C3H4O2 and the structural formula CH2=CH-COOH. Acrylic acid is a very important organic chemical raw material and an important derivative of propylene. It is mainly used to produce acrylic esters (such as methyl acrylate, ethyl acrylate, butyl acrylate, etc.), and further produce a variety of acrylic resin products, which can be widely used in coatings, chemical fibers, textiles, leather, adhesives, acrylic rubber and other fields.
[0003] The main methods for preparing acrylic acid include lactic acid dehydration method, high-pressure Rape method, β-propiolactone method, acrylonitrile hydrolysis method, cyanoethanol method, and propylene oxidation method. Lactic acid dehydration method is that lactic acid undergoes intramolecular dehydration reaction in the presence of a catalyst to produce acrylic acid. High-pressure Rape method is that acetylene dissolved in tetrahydrofuran reacts with carbon monoxide and water in the presence of a catalyst composed of nickel bromide and copper bromide to produce acrylic acid. β-propiolactone method is that acetic acid is first cracked into ketene, ketene reacts with anhydrous formaldehyde to produce β-propiolactone, and β-propiolactone is isomerized into acrylic acid under the action of phosphoric acid catalyst. Acrylonitrile hydrolysis method is that acrylonitrile is first hydrolyzed in the presence of sulfuric acid catalyst to produce acrylamide sulfate, and then hydrolyzed in the second step to produce acrylic acid. The cyanoethanol method uses chloroethanol and sodium cyanide as raw materials, first reacts to produce cyanoethanol, and cyanoethanol undergoes hydrolysis reaction in the presence of sulfuric acid to produce acrylic acid. If the hydrolysis reaction is carried out in methanol, methyl acrylate is produced.
[0004] The propylene oxidation process is currently the most widely used acrylic acid preparation process. It is a process in which propylene reacts with oxygen in the air under the action of a catalyst to first generate acrolein, which is then further oxidized to generate acrylic acid. In this acrylic acid preparation process, the first step is to mix propylene, air, and water vapor and react to generate acrolein in the presence of a catalyst.
[0005] Main reaction:
[0006] CH2=CHCH3+O2→CH2=CHCHO+H2O
[0007] Side effects:
[0008] 4CH2=CHCH3+15O2→6CO+6CO2+12H2O
[0009] 2CH2=CHCH3+5O2→2CH3COOH+2CO2+2H2O
[0010] The second step is the oxidation of acrolein with air and water vapor in the presence of a catalyst to produce acrylic acid.
[0011] Main reaction:
[0012] 2CH2=CHCHO+O2→2CH2=CHCOOH
[0013] Side effects:
[0014] 4CH2=CHCHO+11O2→6CO+6CO2+8H2O
[0015] 4CH2=CHCHO+O2+H2O→4CH2=O+4CH2CH=O
[0016] Since the process is carried out in steps, that is, propylene is first oxidized to acrolein, and acrolein is then oxidized to acrylic acid, the catalyst and reaction conditions can be selected specifically according to the reaction characteristics of each step, and the product yield is good.
[0017] CN88104316.8 discloses a catalyst for preparing acrylic acid by gas phase catalytic oxidation of acrolein, which contains an active substance represented by the following formula:
[0018] Mo (a) V (b) A (c) B (d) C (e) D (f) O (x)
[0019] wherein Mo represents molybdenum, V represents vanadium, A represents at least one element selected from tungsten and niobium, B represents at least one element selected from the group consisting of iron, copper, bismuth, chromium, antimony and thallium, C represents at least one element selected from alkali metals and alkaline earth metals, D represents at least one element selected from silicon, aluminum and titanium, and O represents oxygen; the specific surface area of the catalyst is 0.50 to 15.0 m 2 / g, the porosity is 0.10 to 0.90 cc / g, and the pore size distribution is concentrated in the range of 0.1 to less than 1.0 μm, 1.0 to less than 10.0 μm and 10.0 to 100 μm.
[0020] CN95105259.4 discloses a catalyst used in the gas phase oxidation of molecular oxygen-containing gas and acrolein to produce acrylic acid, which comprises a catalyst of the following formula (I):
[0021] MO a V b W c Cu d X e Y f (I)
[0022] The oxide or composite oxide composed of the metal elements represented by Mg is molybdenum, V is vanadium, W is tungsten, Cu is copper, X is at least one element selected from the group consisting of zirconium, titanium and cerium, and Y is at least one element selected from the group consisting of magnesium, calcium, strontium and barium.
[0023] CN200510007929.8 discloses a catalyst for preparing acrylic acid by catalytic gas-phase oxidation of acrolein with molecular oxygen, the catalyst comprising molybdenum and vanadium, and also comprising a volatile catalyst poison component in an amount of 10 to 100 ppb by mass as measured by ion chromatography.
[0024] CN201010513699.3 discloses a catalyst for preparing acrylic acid by oxidation of acrolein and a preparation method thereof, wherein the catalyst is prepared by using at least one selected from SiO2, Al2O3 or TiO2 as a carrier and containing an active component represented by the following general formula: Mo 12 V a X b Y c Z d Q e O x Wherein X is at least one selected from W, Cr, and Nb; Y is at least one selected from Cu, Fe, Ni, Co, and Mn; Z is at least one selected from Sb and Bi; and Q is at least one selected from Li, Na, K, Rb, Cs, Mg, Ca, and Sr.
[0025] CN201310585693.0 discloses a method for preparing acrylic acid by selective oxidation of acrolein, wherein a fixed bed reactor is used, the reaction raw materials are preheated in a preheater at a temperature above 150°C before entering the reactor, the salt bath temperature is 240-270°C, and the air velocity is 800-2300h / min. -1 The feed composition is: 8-16 volume % of acrolein, 11-21% of water vapor, 9-22 volume % of oxygen, and 60-74 volume % of nitrogen; the fixed bed reactor is equipped with an oxidation catalyst, the catalyst contains molybdenum, vanadium, nickel, copper, strontium and tungsten elements, and the catalyst also contains magnesium aluminate lanthanum oxide.
[0026] CN201410782241.6 discloses a catalyst for producing acrylic acid by oxidation of acrolein and a preparation method thereof, wherein the catalyst for producing acrylic acid by oxidation of acrolein is characterized in that Mo 12 V a W b M c Si d O xDefinition, wherein Mo, V, and W are active components of the catalyst; the carrier Si is derived from mesoporous silica; the auxiliary agent M is selected from at least one of Cu, Fe, Sb, Ce, Co, and Ni; a, b, c, d, and x represent the atomic number of each element, with the atomic number of Mo being 12, the value of V being a being 2 to 6; the value of W being b being 1 to 3; the value of M being c being 0.1 to 3; the value of Si being d being 20 to 100, and the value of O being x being determined by the atomic number of other elements.
[0027] CN201610225886.9 discloses a catalyst for the oxidation of acrolein to produce acrylic acid, which comprises the following components by weight: A: 40-80 parts of at least one carrier selected from SiO2, Al2O3, ZrO2 or TiO2; and B: 20-60 parts of the active component Mo supported thereon. 12 V a Q n Y f O g ; wherein Mo, V and O represent the elements molybdenum, vanadium and oxygen; Q represents at least one element selected from Cr, Cu, Mn, W, Sb and Ag; Y is at least one element selected from alkali metals or alkaline earth metals; a, n, f and g represent the atomic ratios of their respective elements, based on the atomic ratio of Mo element being 12, the value range of a is 0.5 to 4.0, the value range of n is 0.1 to 16.0, the value range of f is 0 to 1.0, and g is the number of oxygen atoms required to satisfy the total valence of other elements.
[0028] CN201910911357.8 discloses a catalyst for the oxidation of acrolein to produce acrylic acid, a preparation method and an application thereof, wherein the active component of the catalyst is generally expressed as: VMo a Fe b Bi c X d Z e O f , wherein X is one or more selected from Al, Ga, Ge, In, Sn, Sb, TI, Pb, Sc, Ti, Y, Zr, Nb, Hf, Ta, Cr, W, Mn, Tc, Re, Ru, Os, Co, Rh, Ir, Ni, Pd, Pt, Cu, Ag, Au, Zn, Cd, La, Ce, Pr, Nd and Sm, and Z is one or more selected from Li, Na, K, Rb, Cs, Be, Mg, Ca, Sr and Ba.
[0029] CN202011105017.5 discloses a catalyst for preparing acrylic acid by oxidation of acrolein, a preparation method and application thereof, and the general formula of the components of the catalyst is: VMo a Wb X c Y d Cu e (AlPO4) f O g , wherein X is at least one selected from Sb, Nb, Cr and Ta, and Y is at least one selected from Li, K, Na and Rb.
[0030] In the two-step process of preparing acrylic acid by catalytic oxidation of propylene, after the completion of propylene oxidation to prepare acrolein, whether acrolein can be effectively converted into acrylic acid is the key to the entire preparation of acrylic acid, which will directly affect the yield of acrylic acid. At the same time, the stability of the catalyst is also very critical. The existing catalysts for preparing acrylic acid by oxidation of acrolein have certain problems to be improved in terms of the structural stability of the catalyst and the yield of acrylic acid. Summary of the invention
[0031] In view of the problems in the prior art, the present invention first provides a catalyst for preparing acrylic acid by oxidation of acrolein, the atomic composition of which is Mo a V b Cu c Sb d W e Si f C g O h , a+b+c+d+e+f+g+h=100, 0.4≤a≤10, 0.1≤b≤5.0, 0.1≤c≤4.0, 0.1≤d≤4.0, 0.1≤e≤1.0, 0.5≤f≤20, 20≤g≤85, h is the remainder, with SiO2 crystal form, the catalyst includes small nanoparticles and irregular large particles, infrared spectrum at 1118cm -1 、902cm -1 Displays Si-O stretching and bending vibrations, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0032] Furthermore, the atomic content of molybdenum is 0.5≤a≤8.0, or 1.0, 2.0, 5.0, or 6.0.
[0033] Furthermore, the atomic content of vanadium is 0.2≤b≤4.0, or 0.5, 1.0, 2.0, 2.5, or 3.0.
[0034] Furthermore, the atomic content of copper is 0.3≤c≤3.0, or 0.5, 1.0, 1.5, 2.0, or 2.5.
[0035] Furthermore, the atomic content of antimony is 0.2≤d≤3.0, or 0.5, 1.0, 2.0, or 2.5.
[0036] Furthermore, the atomic content of tungsten is 0.2≤e≤0.9, or 0.3, 0.5, 0.7, or 0.8.
[0037] Furthermore, the atomic content of silicon is 0.7≤f≤15, or 2.0, 5.0, 7.0, 10, 12, or 14.
[0038] Furthermore, the atomic content of carbon is 12≤f≤60, or 15, 20, 30, 40, or 50.
[0039] Furthermore, infrared testing of the catalyst showed that it had a -1 Stretching vibration of Mo-O-Mo bond, 734 cm - 1 WO bond or Sb-O stretching vibration.
[0040] Furthermore, the particle size of the nanoparticles in the catalyst is 5-80 nm, or 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, or 70 nm.
[0041] Furthermore, the particle size of the irregular large particles in the catalyst is greater than 80 nm and less than or equal to 600 nm, or is 550 nm, 500 nm, 450 nm, 400 nm, 350 nm, or 300 nm.
[0042] The present invention also provides a process for preparing a catalyst for preparing acrylic acid by oxidation of acrolein, wherein the atomic composition is Mo a V b Cu c Sb d W e Si f C g O h , a+b+c+d+e+f+g+h=100, 0.4≤a≤10, 0.1≤b≤5.0, 0.1≤c≤4.0, 0.1≤d≤4.0, 0.1≤e≤1.0, 0.5≤f≤20, 20≤g≤85, h is the remainder, having a SiO2 crystal form, the catalyst includes small nanoparticles and irregular large particles, and the preparation method includes:
[0043] Step (1): Prepare solution
[0044] Dissolve a tungsten source and an organic acid in water, stir to dissolve, add a molybdenum source and a vanadium source, stir to dissolve, and obtain a solution A;
[0045] Dissolve the copper source and the strontium source in water, stir and dissolve to obtain solution B;
[0046] Step (2): Solution mixing reaction
[0047] Add solution B to solution A, stir and mix, heat, evaporate water until the material becomes viscous, and filter to remove the remaining water;
[0048] Step (3): Drying and crushing
[0049] The material obtained in step (2) is dried to obtain a block material, which is crushed by a pulverizer to obtain a primary powder;
[0050] Step (4): Molding
[0051] Adding carbon powder, graphite, antimony source, sesbania powder, silicon source, and appropriate amount of water to the primary powder, stirring and kneading, and forming to obtain a hollow cylindrical product;
[0052] Step (5): Calcination
[0053] The hollow cylindrical product is calcined in a mesh belt furnace to obtain a catalyst product.
[0054] Furthermore, the tungsten source is one or both of ammonium metatungstate and ammonium tungstate.
[0055] Furthermore, the organic acid is one or two of tartaric acid, citric acid and malic acid.
[0056] Furthermore, the molybdenum source is one or two of ammonium molybdate, molybdenum trioxide, molybdenum nitrate, molybdic acid and sodium molybdate.
[0057] Furthermore, the vanadium source is ammonium metavanadate.
[0058] Furthermore, the copper source is one or two of copper nitrate, copper sulfate, copper chloride, and basic copper carbonate.
[0059] Furthermore, the strontium source is one or two of strontium nitrate, strontium chloride and strontium sulfate.
[0060] Furthermore, the antimony source is one or both of antimony trioxide and antimony pentoxide.
[0061] Furthermore, the silicon source is one or both of silicon micropowder and silica sol.
[0062] Furthermore, in step (3), the drying temperature is 80-150°C, or 90°C, 100°C, 110°C, 120°C, 130°C, or 140°C; the drying time is 10-50h, or 15h, 20h, 25h, 30h, or 40h.
[0063] Furthermore, in step (4), the forming includes preforming.
[0064] Furthermore, in step (5), the calcination temperature is 300-600°C, or 350°C, 400°C, 450°C, 500°C, 550°C; the calcination time is 10-50h, or 15h, 20h, 25h, 30h, 40h.
[0065] The present invention also provides application of the catalyst in preparing acrylic acid from acrolein.
[0066] The present invention also provides a method for preparing acrylic acid, comprising reacting acrolein with an oxidizing gas containing oxygen in the presence of a catalyst, wherein the catalyst is the above-mentioned catalyst for preparing acrylic acid by oxidation of acrolein or the catalyst for preparing acrylic acid by oxidation of acrolein prepared by the above-mentioned method.
[0067] Furthermore, the oxidizing gas may be pure oxygen, oxygen-enriched gas, or air.
[0068] Furthermore, in terms of volume ratio, acrolein:air=1:(1-5).
[0069] In order to make the reaction more stable and controllable, it is preferably carried out in the presence of a diluent gas phase material such as water vapor.
[0070] Furthermore, the reaction temperature is 100-500°C, or 200°C, 300°C, or 400°C.
[0071] Furthermore, the reaction pressure may be 0.01 to 0.05 MPa (gauge pressure).
[0072] Furthermore, in the raw material gas composed of acrolein, air and water vapor, the volume ratio of acrolein:air:water vapor=1:(1-5):(0.5-4).
[0073] Beneficial effects of the present invention:
[0074] The catalyst for preparing acrylic acid by oxidizing acrolein has simple preparation process, good crystallinity, SiO2 crystal form and high catalytic activity.
[0075] The catalyst for preparing acrylic acid by oxidation of acrolein shows good composite ability, can improve the dispersion and fixation of active components, make the components more evenly dispersed, and improve the yield of acrolein.
[0076] The catalyst for preparing acrylic acid by oxidizing acrolein has good structural stability, thereby improving the mass transfer and heat transfer performance of the catalyst, so that the catalyst has high acrolein conversion rate and acrylic acid selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0077] Figure 1 This is the XRD test diagram of the catalyst in Example 1.
[0078] Figure 2 This is the infrared test image of the catalyst in Example 1.
[0079] Figure 3 This is a SEM test image of the catalyst of Example 1.
[0080] Figure 4 This is the TEM test image of the catalyst in Example 1.
[0081] Figure 5 This is the EDS test chart of the catalyst in Example 1.
[0082] Figure 6 This is the SEM test image of the catalyst in Example 2.
[0083] Figure 7 This is the TEM test image of the catalyst in Example 2.
[0084] Figure 8 This is the EDS test chart of the catalyst in Example 2.
[0085] Fig. 9 This is the SEM test image of the catalyst in Example 3.
[0086] Fig.10 This is the TEM test image of the catalyst in Example 3.
[0087] Fig.11 This is the EDS test chart of the catalyst in Example 3.
[0088] Fig.12 This is the SEM test image of the catalyst of Example 4.
[0089] Fig.13 This is the TEM test image of the catalyst of Example 4.
[0090] Fig.14 This is the EDS test chart of the catalyst in Example 4.
[0091] Fig.15 This is the SEM test picture of the catalyst in Example 5.
[0092] Fig.16 This is the TEM test image of the catalyst in Example 5.
[0093] Fig.17 This is the SEM test picture of the catalyst of Example 6.
[0094] Fig.18 This is the TEM test image of the catalyst of Example 6. DETAILED DESCRIPTION
[0095] In order to make it easier to understand the structure of the present invention and the functional features and advantages that can be achieved, the following will be combined with the preferred embodiments of the present invention and described in detail as follows:
[0096] 1. XRD test:
[0097] Instrument name: X-ray diffractometer
[0098] Model: D8 ADVANCE
[0099] Test conditions: 10-90°, CU target; wavelength: 1.54 angstroms
[0100] 2. Infrared test:
[0101] Instrument name: Fourier transform infrared spectrometer
[0102] Model: German Bruker VERTEX 70
[0103] Test conditions: Wave number range: 4000-400cm -1 ; Resolution: 2cm -1 ; Number of scans: 32 times.
[0104] 3. SEM test:
[0105] Instrument name: Scanning electron microscope
[0106] Model: Zeiss Sigma 300
[0107] Test conditions: Acceleration voltage: 10kV
[0108] 4. HRTEM test:
[0109] Instrument name: Field emission transmission electron microscope
[0110] Model:TECNAL F20
[0111] Test conditions: Acceleration voltage: 200kV
[0112] 5. EDS test:
[0113] Instrument name: Scanning electron microscope and energy dispersive X-ray fluorescence spectrometer
[0114] The test conditions refer to GB / T 25189-2010 Determination method of quantitative analysis parameters of microbeam analysis scanning electron microscope energy dispersive spectrometer.
[0115] The raw materials used in the catalyst preparation process of the present invention are all purchased commercially.
[0116] Parts in the present invention, unless otherwise specified, are parts by weight.
[0117] The preferred embodiments of the present invention are described below. The preferred embodiments described herein are only used to illustrate and explain the present invention and are not used to limit the present invention.
[0118] Example 1
[0119] A process for preparing a catalyst for preparing acrylic acid by oxidation of acrolein, comprising:
[0120] Step (1): Prepare solution
[0121] Dissolve 35 parts of ammonium metatungstate and 36 parts of tartaric acid in water, stir to dissolve, add 196 parts of ammonium molybdate and 57 parts of ammonium metavanadate, stir to dissolve, and obtain solution A;
[0122] Dissolve 48 parts of copper nitrate and 5 parts of strontium nitrate in water and stir to dissolve to obtain solution B;
[0123] Step (2): Solution mixing reaction
[0124] Add solution B to solution A, stir and mix, heat to 80°C, evaporate water until the material becomes viscous, and filter to remove the remaining water;
[0125] Step (3): Drying and crushing
[0126] The material obtained in step (2) is dried at a temperature of 100° C. for 25 h to obtain a block material, which is crushed with a pulverizer to obtain a primary powder;
[0127] Step (4): Molding
[0128] 200 parts of primary powder are added to 100 parts of carbon powder, 6 parts of graphite, 35 parts of antimony trioxide, 6 parts of antimony pentoxide, 2 parts of sesbania powder, 3 parts of silicon powder, and an appropriate amount of water, stirred and kneaded, and molded to obtain a hollow cylindrical product;
[0129] Step (5): Calcination
[0130] The hollow cylindrical product was calcined in a rotary kiln at a temperature of 430° C. for 10 h to obtain a catalyst product.
[0131] The catalyst product of Example 1 has a hollow cylindrical shape with dimensions of φ×L=(4.0±0.15mm)×(3.5±0.2mm) and a bulk density of 1.30±0.05t / m 3 , compressive strength 100N / grain, porosity 0.18cm 3 / g.
[0132] The prepared catalyst was tested, such as Figure 1-5 As shown, Figure 1Display XRD test results, Figure 2 Display infrared test results, Figure 3 Display SEM test results, Figure 4 Display TEM test results, Figure 5 Displays EDS test results.
[0133] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0134] The catalyst includes large irregular particles with poor dispersibility, with a particle size of 80 to 150nm; and small nanoparticles with a uniform particle size of about 40nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0135] Infrared testing of the catalyst showed that it has a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0136] The EDS spectrum analysis results of the catalyst are as follows:
[0137]
[0138]
[0139] That is, the atomic composition of the catalyst is Mo 0.96 V 0.41 Cu 0.30 Sb 0.24 W 0.16 Si 0.72 C 84.59 O 12.61 , which does not contain elemental nitrogen N.
[0140] Example 2
[0141] A process for preparing a catalyst for preparing acrylic acid by oxidation of acrolein, comprising:
[0142] Step (1): Prepare solution
[0143] Dissolve 25 parts of ammonium metatungstate and 30 parts of tartaric acid in water, stir to dissolve, add 150 parts of ammonium molybdate and 50 parts of ammonium metavanadate, stir to dissolve, and obtain solution A;
[0144] Dissolve 50 parts of copper sulfate and 6 parts of strontium nitrate in water and stir to dissolve to obtain solution B;
[0145] Step (2): Solution mixing reaction
[0146] Add solution B to solution A, stir and mix, heat to 85°C, evaporate water until the material becomes viscous, and filter to remove the remaining water;
[0147] Step (3): Drying and crushing
[0148] The material obtained in step (2) is dried at 95° C. for 30 h to obtain a block material, which is crushed with a pulverizer to obtain a primary powder;
[0149] Step (4): Molding
[0150] 200 parts of primary powder are added with 40 parts of carbon powder, 6 parts of graphite, 35 parts of antimony trioxide, 6 parts of antimony pentoxide, 2 parts of sesbania powder, 3 parts of silicon powder, and an appropriate amount of water, stirred and kneaded, and formed to obtain a hollow cylindrical product;
[0151] Step (5): Calcination
[0152] The hollow cylindrical product was calcined in a rotary kiln at a temperature of 400° C. for 10 h to obtain a catalyst product.
[0153] The catalyst product of Example 2 has a hollow cylindrical shape with dimensions of φ×L=(4.0±0.15mm)×(3.5±0.2mm) and a bulk density of 1.40±0.05t / m 3 , compressive strength 100N / grain, porosity 0.19cm 3 / g.
[0154] The prepared catalyst was tested, such as Figure 6-8 As shown, Figure 6 Display SEM test results, Figure 7 Display TEM test results, Figure 8 Displays EDS test results.
[0155] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0156] The catalyst includes large irregular particles with poor dispersibility, with a particle size of 100 to 200nm; and small nanoparticles with a uniform particle size of about 50nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0157] Infrared testing of the catalyst showed that it had a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0158] The EDS spectrum analysis results of the catalyst are as follows:
[0159]
[0160] That is, the atomic composition of the catalyst is Mo 6.81 V 2.31 Cu 1.24 Sb 1.52 W 0.69 Si 8.76 C 36.11 O 42.56 , which does not contain elemental nitrogen N.
[0161] Example 3
[0162] A process for preparing a catalyst for preparing acrylic acid by oxidation of acrolein, comprising:
[0163] Step (1): Prepare solution
[0164] Dissolve 40 parts of ammonium tungstate and 36 parts of tartaric acid in water, stir to dissolve, add 200 parts of ammonium molybdate and 60 parts of ammonium metavanadate, stir to dissolve, and obtain solution A;
[0165] Dissolve 60 parts of copper nitrate and 8 parts of strontium nitrate in water and stir to dissolve to obtain solution B;
[0166] Step (2): Solution mixing reaction
[0167] Add solution B to solution A, stir and mix, heat to 70°C, evaporate water until the material becomes viscous, and filter to remove the remaining water;
[0168] Step (3): Drying and crushing
[0169] The material obtained in step (2) is dried at 80° C. for 35 h to obtain a block material, which is crushed with a pulverizer to obtain a primary powder;
[0170] Step (4): Molding
[0171] 200 parts of primary powder are added with 120 parts of carbon powder, 5 parts of graphite, 40 parts of antimony trioxide, 6 parts of antimony pentoxide, 2 parts of sesbania powder, 10 parts of silicon powder, and an appropriate amount of water, stirred and kneaded, and formed to obtain a hollow cylindrical product;
[0172] Step (5): Calcination
[0173] The hollow cylindrical product was calcined in a mesh belt furnace at a temperature of 400° C. for 10 h to obtain a catalyst product.
[0174] The catalyst product of Example 3 has a hollow cylindrical shape with dimensions of φ×L=(4.0±0.15mm)×(3.5±0.2mm) and a bulk density of 1.35±0.05t / m 3 , compressive strength 103N / grain, porosity 0.20cm 3 / g.
[0175] The prepared catalyst was tested, such as Figure 9-11 As shown, Fig. 9 Display SEM test results, Fig.10 Display TEM test results, Fig.11 Displays EDS test results.
[0176] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0177] The catalyst includes large irregular particles with poor dispersibility, with a particle size of 80 to 180nm; and small nanoparticles with a uniform particle size of about 60nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0178] Infrared testing of the catalyst showed that it has a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0179] The EDS spectrum analysis results of the catalyst are as follows:
[0180]
[0181] That is, the atomic composition of the catalyst is Mo 6.15 V 2.30 Cu 1.06 Sb 1.38 W 0.84 Si 14.78 C 35.52 O 37.98 , which does not contain elemental nitrogen N.
[0182] Example 4
[0183] A process for preparing a catalyst for preparing acrylic acid by oxidation of acrolein, comprising:
[0184] Step (1): Prepare solution
[0185] Dissolve 60 parts of ammonium tungstate and 36 parts of malic acid in water, stir to dissolve, add 200 parts of ammonium molybdate and 60 parts of ammonium metavanadate, stir to dissolve, and obtain solution A;
[0186] Dissolve 60 parts of copper chloride and 8 parts of strontium nitrate in water, stir and dissolve to obtain solution B;
[0187] Step (2): Solution mixing reaction
[0188] Add solution B to solution A, stir and mix, heat to 70°C, evaporate water until the material becomes viscous, and filter to remove the remaining water;
[0189] Step (3): Drying and crushing
[0190] The material obtained in step (2) is dried at 80° C. for 35 h to obtain a block material, which is crushed with a pulverizer to obtain a primary powder;
[0191] Step (4): Molding
[0192] 200 parts of primary powder are added with 100 parts of carbon powder, 5 parts of graphite, 40 parts of antimony trioxide, 6 parts of antimony pentoxide, 2 parts of sesbania powder, 8 parts of silicon powder, and an appropriate amount of water, stirred and kneaded, and formed to obtain a hollow cylindrical product;
[0193] Step (5): Calcination
[0194] The hollow cylindrical product was calcined in a mesh belt furnace at a temperature of 400° C. for 10 h to obtain a catalyst product.
[0195] The catalyst product of Example 4 has a hollow cylindrical size of φ×L=(4.0±0.15mm)×(3.5±0.2mm) and a bulk density of 1.35±0.05t / m 3 , compressive strength 103N / grain, porosity 0.20cm 3 / g.
[0196] The prepared catalyst was tested, such as Figure 12-14 As shown, Fig.12 Display SEM test results, Fig.13 Display TEM test results, Fig.14 Displays EDS test results.
[0197] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0198] The catalysts include large irregular particles with poor dispersibility, ranging from 120 to 300 nm, and small nanoparticles with a uniform particle size of about 60 nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0199] Infrared testing of the catalyst showed that it has a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0200] The EDS spectrum analysis results of the catalyst are as follows:
[0201]
[0202]
[0203] That is, the atomic composition of the catalyst is Mo 5.64 V 2.24 Cu 1.28 Sb 1.38 W 0.79 Si 18.08 C 27.13 O 38.97 , which does not contain elemental nitrogen N.
[0204] Example 5
[0205] A process for preparing a catalyst for preparing acrylic acid by oxidation of acrolein, comprising:
[0206] Step (1): Prepare solution
[0207] Dissolve 60 parts of ammonium metatungstate and 36 parts of citric acid in water, stir to dissolve, add 180 parts of ammonium molybdate and 60 parts of ammonium metavanadate, stir to dissolve, and obtain solution A;
[0208] Dissolve 60 parts of copper nitrate and 8 parts of strontium nitrate in water and stir to dissolve to obtain solution B;
[0209] Step (2): Solution mixing reaction
[0210] Add solution B to solution A, stir and mix, heat to 70°C, evaporate water until the material becomes viscous, and filter to remove the remaining water;
[0211] Step (3): Drying and crushing
[0212] The material obtained in step (2) is dried at 80° C. for 35 h to obtain a block material, which is crushed with a pulverizer to obtain a primary powder;
[0213] Step (4): Molding
[0214] 200 parts of primary powder are added with 100 parts of carbon powder, 5 parts of graphite, 40 parts of antimony trioxide, 6 parts of antimony pentoxide, 2 parts of sesbania powder, 8 parts of silicon powder, and an appropriate amount of water, stirred and kneaded, and formed to obtain a hollow cylindrical product;
[0215] Step (5): Calcination
[0216] The hollow cylindrical product was calcined in a mesh belt furnace at a temperature of 400° C. for 10 h to obtain a catalyst product.
[0217] The catalyst product of Example 4 has a hollow cylindrical size of φ×L=(4.0±0.15mm)×(3.5±0.2mm) and a bulk density of 1.35±0.05t / m 3 , compressive strength 103N / grain, porosity 0.25cm 3 / g.
[0218] The prepared catalyst was tested, such as Figure 15-16 As shown, Fig.15 Display SEM test results, Fig.16 Displays TEM test results.
[0219] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0220] The catalyst includes large irregular particles with poor dispersibility, with a particle size of 150 to 400nm; and small nanoparticles with a uniform particle size of about 80nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0221] Infrared testing of the catalyst showed that it has a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0222] Example 6
[0223] A preparation process for preparing acrylic acid catalyst by oxidation of acrolein, which differs from Example 1 in that the raw material composition and weight parts are adjusted to 30 parts of ammonium metatungstate, 36 parts of citric acid, 200 parts of ammonium molybdate, 60 parts of ammonium metavanadate, 45 parts of copper nitrate, and 6 parts of strontium nitrate, and the rest remain unchanged.
[0224] The prepared catalyst was tested, such as Figure 17-18 As shown, Fig.17 Display SEM test results, Fig.18 Displays TEM test results.
[0225] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0226] The catalyst includes large irregular particles with poor dispersibility, with a particle size of 150 to 350nm; and small nanoparticles with a uniform particle size of about 60nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0227] Infrared testing of the catalyst showed that it has a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0228] Example 7
[0229] A preparation process of a catalyst for preparing acrylic acid by oxidation of acrolein, which differs from Example 1 in that the raw material composition and weight parts are adjusted to 40 parts of ammonium metatungstate, 33 parts of malic acid, 210 parts of ammonium molybdate, 70 parts of ammonium metavanadate, 60 parts of copper nitrate, and 10 parts of strontium nitrate, and the rest remain unchanged.
[0230] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0231] The catalysts include large irregular particles with poor dispersibility, ranging in size from 120 to 350 nm, and small nanoparticles with a uniform size of about 65 nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0232] Infrared testing of the catalyst showed that it has a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm-1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0233] Example 8
[0234] A preparation process of a catalyst for preparing acrylic acid by oxidation of acrolein, which differs from Example 1 in that the raw material composition and weight parts are adjusted to 40 parts of ammonium metatungstate, 33 parts of malic acid, 210 parts of ammonium molybdate, 70 parts of ammonium metavanadate, 60 parts of copper nitrate, and 10 parts of strontium nitrate; 80 parts of carbon powder, 8 parts of graphite, 35 parts of antimony trioxide, 6 parts of antimony pentoxide, 2 parts of sesbania powder, and 10 parts of silicon powder are added during the molding process, and the rest remain unchanged.
[0235] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0236] The catalyst includes large irregular particles with poor dispersibility, with a particle size of 80 to 300nm; and small nanoparticles with a uniform particle size of about 50nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0237] Infrared testing of the catalyst showed that it has a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0238] Example 9
[0239] A preparation process of a catalyst for preparing acrylic acid by oxidation of acrolein, which differs from Example 1 in that the raw material composition and weight parts are adjusted to 50 parts of ammonium metatungstate, 30 parts of malic acid, 170 parts of ammonium molybdate, 80 parts of ammonium metavanadate, 65 parts of copper nitrate, and 10 parts of strontium nitrate; 80 parts of carbon powder, 5 parts of graphite, 35 parts of antimony trioxide, 6 parts of antimony pentoxide, 3 parts of sesbania powder, and 10 parts of silicon powder are added during the molding process, and the rest remain unchanged.
[0240] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0241] The catalyst includes large irregular particles with poor dispersibility, with a particle size of 100 to 270nm; and small nanoparticles with a uniform particle size of about 60nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0242] Infrared testing of the catalyst showed that it had a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0243] Example 10
[0244] A preparation process of a catalyst for preparing acrylic acid by oxidation of acrolein, which differs from Example 1 in that the raw material composition and weight parts are adjusted to 80 parts of ammonium metatungstate, 30 parts of citric acid, 180 parts of ammonium molybdate, 80 parts of ammonium metavanadate, 60 parts of copper nitrate, and 10 parts of strontium nitrate; 100 parts of carbon powder, 5 parts of graphite, 35 parts of antimony trioxide, 6 parts of antimony pentoxide, 3 parts of sesbania powder, and 10 parts of silica sol are added during the molding process, and the rest remain unchanged.
[0245] According to the test and analysis of the catalyst, it can be determined that the catalyst has good crystallinity and has the crystal form of SiO2.
[0246] The catalysts include large irregular particles with poor dispersibility, with a particle size of 110 to 270 nm, and small nanoparticles with a uniform particle size of about 50 nm. All particles are crystalline, with large particles having poor dispersibility and small particles having good dispersibility.
[0247] Infrared testing of the catalyst showed that it had a -1 、902cm -1 Si-O stretching and bending vibration, 799 cm -1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration, 583 cm -1 The stretching vibration peak of Cu-O bond.
[0248] Comparative Example 1
[0249] A preparation process of a catalyst for preparing acrylic acid by oxidation of acrolein, which is different from Example 1 in that silicon micropowder is not added.
[0250] Comparative Example 2
[0251] A preparation process of a catalyst for preparing acrylic acid by oxidation of acrolein, which is different from Example 1 in that no carbon powder is added.
[0252] Comparative Example 3
[0253] A preparation process of a catalyst for preparing acrylic acid by oxidizing acrolein, which is different from Example 1 in that copper nitrate is not added.
[0254] The catalysts of Examples 1-10 of the present invention and Comparative Examples 1-2 were evaluated for catalytic reaction of acrolein.
[0255] The catalyst evaluation conditions are as follows:
[0256] Reactor: Fixed bed reactor, inner diameter 20 mm, reactor length 550 mm
[0257] Catalyst: 90 g
[0258] Reaction temperature: 280℃
[0259] Reaction pressure: 0.02MPa (gauge pressure)
[0260] Acrolein: air: water vapor (volume ratio) = 1:3:2
[0261] Total volume space velocity of raw materials: 1400h -1
[0262] The reaction products were analyzed by gas chromatography (Agilent 7890A).
[0263] Acrolein conversion and acrylic acid yield are defined as follows:
[0264] Acrolein conversion rate = (molar amount of acrolein reacted / total molar amount of acrolein added) × 100%;
[0265] Acrylic acid yield = (molar amount of acrylic acid produced / molar amount of total acrolein added) × 100%.
[0266] Table 1 Evaluation results of Examples 1-10 and Comparative Examples 1-3
[0267] catalyst Acrolein conversion rate Acrylic acid yield Example 1 99.1% 90.2% Example 2 99.3% 89.1% Example 3 99.0% 91.3% Example 4 99.0% 90.5% Example 5 98.9% 90.5% Example 6 99.2% 90.3% Example 7 99.5% 89.6% Example 8 99.4% 91.5% Example 9 99.1% 90.8% Example 10 99.2% 91.5% Comparative Example 1 95.4% 85.3% Comparative Example 2 94.9% 86.1% Comparative Example 3 90.8% 85.5%
[0268] The catalysts of Examples 1-10 can still maintain their catalytic activity after 2500 hours of oxidation reaction. It can be seen that the catalyst for preparing acrylic acid by oxidation of acrolein has good catalytic performance, the acrolein conversion rate is as high as 98.9% or more, and the selectivity of acrylic acid can be as high as 89.6% or more.
[0269] The above is only a preferred embodiment of the present invention and is not intended to limit the protection scope of the present invention. All equivalent changes and modifications made according to the content of the present invention are included in the patent scope of the present invention.
Claims
1. A catalyst for preparing acrylic acid by oxidation of acrolein, wherein the atomic composition is Mo a V b Cu c Sb d W e Si f C g O h , a+b+c+d+e+f+g+h=100, 0.4≤a≤10, 0.1≤b≤5.0, 0.1≤c≤4.0, 0.1≤d≤4.0, 0.1≤e≤1.0, 0.5≤f≤20, 20≤g≤85, h is the remainder, with SiO2 crystal form, the catalyst includes small nanoparticles and irregular large particles, infrared spectrum at 1118cm -1 、902cm -1 Displays Si-O stretching and bending vibrations, 583 cm -1 The stretching vibration peak of Cu-O bond.
2. The catalyst according to claim 1, characterized in that Infrared testing of the catalyst showed that it has a - 1 Stretching vibration of Mo-O-Mo bond, 734 cm -1 WO bond or Sb-O stretching vibration.
3. The catalyst according to claim 1, characterized in that The particle size of the nanoparticles in the catalyst is 5-80nm.
4. The catalyst according to claim 1, characterized in that The particle size of the irregular large particles in the catalyst is greater than 80 nm and less than or equal to 600 nm.
5. A process for preparing a catalyst for preparing acrylic acid by oxidation of acrolein, wherein the atomic composition is Mo a V b Cu c Sb d W e Si f C g O h , a+b+c+d+e+f+g+h=100, 0.4≤a≤10, 0.1≤b≤5.0, 0.1≤c≤4.0, 0.1≤d≤4.0, 0.1≤e≤1.0, 0.5≤f≤20, 20≤g≤85, h is the remainder, having a SiO2 crystal form, the catalyst includes small nanoparticles and irregular large particles, and the preparation method includes: Step (1): Prepare solution Dissolve a tungsten source and an organic acid in water, stir to dissolve, add a molybdenum source and a vanadium source, stir to dissolve, and obtain a solution A; Dissolve the copper source and the strontium source in water, stir and dissolve to obtain solution B; Step (2): Solution mixing reaction Add solution B to solution A, stir and mix, heat, evaporate water until the material becomes viscous, and filter to remove the remaining water; Step (3): Drying and crushing The material obtained in step (2) is dried to obtain a block material, which is crushed with a pulverizer to obtain a primary powder; Step (4): Molding Adding carbon powder, graphite, antimony source, sesbania powder, silicon source, and appropriate amount of water to the primary powder, stirring and kneading, and forming to obtain a hollow cylindrical product; Step (5): Calcination The hollow cylindrical product is calcined in a mesh belt furnace to obtain a catalyst product. The catalyst according to claim 1, characterized in that.
6. The process for preparing the catalyst according to claim 5, characterized in that: The organic acid is one or two of tartaric acid, citric acid and malic acid.
7. The process for preparing the catalyst according to claim 5, characterized in that: In step (3), the drying temperature is 80-150° C. and the drying time is 10-50 h.
8. The process for preparing the catalyst according to claim 5, characterized in that: In step (5), the calcination temperature is 300-600° C. and the calcination time is 10-50 hours.
9. Use of the catalyst according to any one of 1 to 4 in the preparation of acrylic acid from acrolein.
10. A method for preparing acrylic acid, comprising reacting acrolein with an oxidizing gas containing oxygen in the presence of a catalyst, wherein: The catalyst is a catalyst for preparing acrylic acid by oxidation of acrolein according to any one of claims 1 to 4 or a catalyst for preparing acrylic acid by oxidation of acrolein prepared by the preparation process according to any one of claims 5 to 8.
Citation Information
Patent Citations
Catalyst for catalytic gas phase oxidation of acrolein and process for producing acrylic acid by catalytic gas phase oxidation using said catalyst
CN100425341C
Catalyst for oxidation of acrolein and process for preparation thereof
CN1020861C
Acrylic acid catalyst prepared by acrolein oxidation and preparation method thereof
CN102451702A
Acrylic acid catalyst prepared through acrolein oxidation and preparation method of acrylic acid catalyst
CN104399483A
Process for Preparing Acrylic Acid by Selective Oxidation of Acrolein
CN104649894B